Mixed sand–mud bedforms produced by transient turbulent flows in the fringe of submarine fans: Indicators of flow transformation. Issue 5 (18th March 2020) - Baker, Megan L.; Baas, Jaco H.
Abstract: The fringe of fine‐grained deep‐marine systems often exhibits complex sedimentary facies and facies associations, because the presence of clay promotes the development of transient turbulent flows with complex depositional properties. Relatively little is known about the variation of current‐induced sedimentary structures found within these facies. This study provides the first comprehensive description and interpretation of mixed sandstone–mudstone bedforms observed in the fringe of the mud‐rich submarine fan that makes up the Aberystwyth Grits Group and Borth Mudstone Formation (Wales, UK). Using textural and structural descriptions, 158 bedforms in sediment gravity flow deposits were characterized into three main types: 'classic' sandy current ripples, large current ripples and low‐amplitude bed‐waves. The sandy current ripples comprise clean sandstone, with average heights and lengths of 11 mm and 141 mm, respectively. The large current ripples are composed of mixed sandstone–mudstone and possess greater dimensions than the sandy current ripples, with an average height of 19 mm and an average length of 274 mm. The low‐amplitude bed‐waves are long thin bedforms composed commonly of mixed sandstone–mudstone, with an average height and length of 10 mm and 354 mm, respectively. The large current ripples and low‐amplitude bed‐waves are strikingly similar to experimental bedforms produced under decelerating mixed sand–mud flows and are interpreted to form beneath transitional flows with enhanced and attenuated near‐bed turbulence, respectively. From the fringe to the distal fringe of the fan, the dominant bedform type changed from sandy current ripples, via large current ripples, to low‐amplitude bed‐waves, suggesting that the flows changed from turbulent to increasingly turbulence‐modulated. It is proposed that the flow Reynolds number reduced, reflecting this flow transformation, from a combination of constant or decreasing flow height, flow deceleration from sediment deposition, and increasing flow viscosity due to the shear‐thinning nature of clay‐rich suspensions. Large current ripples and low‐amplitude bed‐waves are likely to be common in the fringe of other submarine fans. The presence and spatial trends in mixed sand–mud bedform types may be an important tool in interpreting fan fringe environments.